Policy Determination in E-Budgeting Implementation by the Government of DKI Jakarta - Indonesia - Hakim, Abdul; Saputra, Ondy Asep; Saleh, Choirul (International Journal of Criminology and Sociology, 2021)
This research discusses and analyzes the deep comprehensiveness of the process of determining and implementing the E-Budgeting Policy by the Government of the Jakarta Migrant Workers; Research methodology uses a qualitative approach. The research results reveal the effectiveness of the role of actors in the process of implementing E-Budgeting policies determined by several factors, namely: the level of understanding of budgeting procedures and mechanisms (APBD), activeness in providing input in the initial process (Musrenbag), and the ability to accommodate the interests of constituents into programs and concrete activities in the RKPD; the legislative role in implementing E-Budgeting can be mapped out by looking at the actions of the executive and executive, namely: first, the interaction of non-professional making models, is a form of meeting between the executive and the legislature to use the power and authority, use of the budget, process and use; secondly, the associative systemic pattern, is a model of executive and legislative relations that is influenced by political, economic, and social systems, so that the process of formulating the General Budget Policy (KUA) and the Budget Priority and Platform (PPAS) is not value-free because it is influenced by the interests and demands of various interest groups. If there are interests from groups that have more political resources and political power compared to other groups, then they are likely to influence budget decisions.